Evaluation of sex‐by‐formulation interaction in bioequivalence studies of efavirenz tablets - González‐Rojano, Esperanza (Br J Clin Pharmacol, 2018)
AIMS: The existence of a sex‐by‐formulation interaction in bioequivalence studies implies that the bioequivalence results (i.e., the test/reference ratio of the pharmacokinetic parameters) obtained in one sex are not similar to those obtained in the other sex. Therefore, results obtained in studies including only males would not be representative of the results that would have been obtained in females and vice versa. Recently, a sex‐by‐formulation interaction has been reported in a study for efavirenz tablets. The purpose of this paper is to investigate whether a sex‐by‐formulation interaction is actually observed in the bioequivalence studies conducted with efavirenz tablets. METHODS: The existence of sex‐by‐formulation interaction was investigated in the two studies conducted in our centre, where the same test and reference products were investigated in a pilot study with 12 subjects and a pivotal study with 36 subjects. RESULTS: In the pilot study, the point estimates for the test/reference ratio of geometrics means of C (max) in females and males were more than 20% different (95.42% vs.79.38%, i.e., 120.21%), but in a subsequent pivotal study the difference was less than 2% (111.14% vs. 109.98%, i.e., 101.66%). CONCLUSIONS: A sex‐by‐formulation interaction is suggested in the study with a small sample size, but it disappears when the study is repeated with a larger sample size. In conclusion, the analysis of subgroups should be conducted with caution when the size of the subgroups is not powered to show bioequivalence. There seems to be no reason to require bioequivalence studies for efavirenz in both sexes.